Regimes dependent speculative trading: Evidence from the United States housing market - Zhenxi Chen (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
This paper investigates the U.S. housing price dynamics from the perspective of speculative trading, in addition to the macro-finance factors such as the stock market, household disposable income and nominal interest rate. It is found that among the speculative investors, fundamental traders drive house price away from the fundamental value. Their trading is weakened in the regime of high nominal interest rate and their behavior even changes to push the price towards the fundamental value when price deviation is large. A second type of speculative traders is momentum traders who believe that the trend of the recent price movement would be persistent. Stock market has a positive effect on the house price. The positive effect of household income becomes pronounced when nominal interest rate is high. When the nominal interest rate is high, house price faces a negative effect from the nominal interest rate and the positive effect of inflation disappears. Among all the factors, speculative trading is the largest market force driving the U.S. housing market which exhibits self-correction in the long run.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: C2; C5; R2; D1; 330; Speculative trading; U.S. housing market; Wealth effect; Money illusion effect